2021
DOI: 10.1111/andr.13010
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐cavernous injection of BOTOX® (50 and 100 Units) for treatment of vasculogenic erectile dysfunction: Randomized controlled trial

Abstract: Background: Erectile dysfunction (ED) is a socioeconomic problem.There are several options for its management including intra-cavernosal injection (ICI).Objective: To compare the safety, efficacy, and durability of ICI of onabotulinum toxin-A (BTX) in different doses (50 and 100 U) against placebo (saline) in the management of vasculogenic ED non-responding to pharmacological therapy (phosphodiesterase type 5 inhibitors or/and ICI of trimix). Materials and Methods:A prospective randomized double-blind placebo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Since the potency of Botox ® and Xeomin ® is identical, they can be compared using a 1:1 conversion ratio [21]. Studies have repeatedly reported the effectiveness of a 100U dose of onabotulinumtoxinA in difficult-to-treat ED [14,16,17]; therefore, we used the same dose of incobotulinumtoxinA in the present study. The conversion ratio between onabotulinumtoxinA (or incobotulinumtoxinA) and abobotulinumtoxinA is more debated [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the potency of Botox ® and Xeomin ® is identical, they can be compared using a 1:1 conversion ratio [21]. Studies have repeatedly reported the effectiveness of a 100U dose of onabotulinumtoxinA in difficult-to-treat ED [14,16,17]; therefore, we used the same dose of incobotulinumtoxinA in the present study. The conversion ratio between onabotulinumtoxinA (or incobotulinumtoxinA) and abobotulinumtoxinA is more debated [20].…”
Section: Discussionmentioning
confidence: 99%
“…The first follow-up assessment was performed 43.5 (34-71) days post-injection. EFdomain score post-injection was 21 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). A total of 28/54 (52%) men responded: their EF domain score was 26 (22)(23)(24)(25)(26)(27)(28)(29), corresponding to an increase of 8 (6-15) points from baseline.…”
Section: Response To the First Incobotulinumtoxina Icimentioning
confidence: 99%
See 3 more Smart Citations